A method for producing a regeneratively heat-resistant and creep-resistant aluminum alloy by semi-solid iron removal
Patent Information
- Application Number
- CN202611471998.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-21
- Publication Date
- 2026-10-27
AI Technical Summary
[0005]针对现有技术的缺陷,本申请的目的在于提供一种半固态除铁制备再生耐热抗蠕变铝合金的方法,旨在解决传统废铝硅合金回收工艺存在的除铁效率低、富铁相控制不足、设备与工艺复杂等问题
(1)本申请提供的半固态除铁制备再生耐热抗蠕变铝合金的方法,通过采用Mn-Ce-La-Ta-Nb五元复合体系并精确控制各组分间的比例关系,结合半固态沉降除铁工艺,有效解决了现有技术中除铁效率低、富铁相控制不足以及回收过程能耗高的技术问题。在除铁方面,Mn与Fe反应生成α-Al(Mn,Fe)Si块状相,避免针状β-AlFeSi脆性相的形成;Ce-La通过晶界吸附将富铁相充分细化,并使其形态由针状向颗粒状转变;Ta-Nb协同形成弥散质点可抑制富铁相在Ta颗粒表面的附着和聚集,避免富铁相局部富集,从而显著提高除铁效率并稳定控制Fe残留量。在半固态沉降方面,将改性后的熔体降温至半固态温度区间,利用富铁相与液态铝硅基体之间的密度差使富铁相向下沉降,实现富铁相的有效分离;同时,半固态沉降在较低温度下进行,相比传统全液态熔炼显著降低了能耗。
Smart Images

Figure CN122979692A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of aluminum-silicon alloy recycling technology, and more specifically, relates to a method for preparing regenerated heat-resistant and creep-resistant aluminum alloys by removing iron in a semi-solid state. Background Technology
[0002] The aluminum-silicon alloy recycling industry is a key path for the global aluminum industry to overcome resource and environmental bottlenecks, achieve value reconstruction, and upgrade its industry. From a resource and environmental perspective, global bauxite reserves are limited. The production of one ton of primary aluminum requires 130,000 to 150,000 kWh of electricity and emits approximately 17 tons of carbon dioxide, contradicting the need for energy conservation and emission reduction. In terms of economic value, recycled aluminum production consumes only 5% of the energy of primary aluminum, reduces carbon emissions by 95%, and lowers production costs by 30% to 50%, demonstrating significant economic benefits. On the market demand side, the trend towards lightweight automobiles, new energy vehicles (motor housings, battery trays), and the aerospace sector are driving explosive growth in demand for high-performance aluminum-silicon alloys. However, the industry currently faces the technical bottleneck of "five highs and one low" in traditional recycling processes: high equipment investment costs, high energy consumption, high environmental pollution, high operational complexity, and high raw material compatibility requirements. Simultaneously, there is the problem of low product performance stability, resulting in over 90% of waste aluminum resources being recycled at a downgraded state, and a high-end aluminum-silicon alloy recycling technology system is still underdeveloped.
[0003] The current aluminum-silicon alloy recycling process has the following shortcomings: (1) Low iron removal efficiency: The iron removal rate of traditional processes is generally <60%, which makes it difficult to reduce the Fe content to the original aluminum grade standard (≤0.2wt%), resulting in Fe residue ≥0.34wt%, which seriously affects the mechanical properties of the recycled alloy. (2) Insufficient control of iron-rich phase: The existing recycling process cannot effectively refine the iron-rich phase. The iron-rich phase particle size is usually ≥15μm, and it is easy to form needle-like β-AlFeSi brittle phase, which significantly reduces the mechanical properties of the recycled alloy. (3) Limited effect of iron removal agent: The existing process can only partially improve the morphology of the iron phase by adding traditional iron removal agents such as Mn or Ce, which makes it difficult to achieve the dual goals of deep iron removal and performance improvement. (4) Complex equipment and process, high recycling energy consumption: The cost of a single traditional stepped crucible exceeds 2,000 yuan, and the maintenance is complicated, the operation threshold is high, and the cleaning time is long (>3h), resulting in low recycling efficiency. At the same time, the existing recycling process generally has problems such as complicated process, high cost, high energy consumption, and large environmental pollution. For example, patent application CN119640072A involves multi-stage melting and Mn-Cr composite iron removal of aluminum-silicon alloy, and applying a vibration field to the casting mold using vibration equipment. By adjusting the amplitude and frequency, the primary iron-rich phase in the mold is vibrated, thus achieving the preparation of low-iron recycled aluminum-silicon alloy. However, this process is complicated, energy-intensive, and generates a large amount of waste residue.
[0004] Therefore, there is an urgent need to develop a waste aluminum-silicon alloy recycling method that is simple in process, low in energy consumption, and can efficiently remove iron, refine the iron-rich phase, and synergistically improve the mechanical properties, heat resistance and creep resistance of the recycled alloy. Summary of the Invention
[0005] In view of the shortcomings of the existing technology, the purpose of this application is to provide a method for preparing recycled heat-resistant and creep-resistant aluminum alloys by removing iron in a semi-solid manner, which aims to solve the problems of low iron removal efficiency, insufficient control of iron-rich phase, and complex equipment and processes in traditional waste aluminum-silicon alloy recycling processes.
[0006] To achieve the above objectives, in a first aspect, this application provides a method for preparing recycled heat-resistant and creep-resistant aluminum alloys through semi-solid iron removal, comprising the following steps: S1. The waste aluminum-silicon alloy is melted to obtain a melt, and then a composite modifier containing Mn, Ce, La, Ta and Nb elements is added. After it is completely melted, it is cooled to obtain a semi-solid slurry, and then semi-solid sedimentation is carried out to remove iron. The mass ratio of Mn to Fe in the waste aluminum-silicon alloy is (0.8~1.5):1, the mass ratio of Ta to Fe in the waste aluminum-silicon alloy is (0.05~0.2):1, and the total amount of Ce and La is 0.1wt%~0.15wt% of the mass of the waste aluminum-silicon alloy; furthermore, the mass ratio of Nb to Ta is (1~1.2):1, and the mass ratio of Ce to La is 2:1. S2. Take the upper melt and cast it to obtain a recycled heat-resistant and creep-resistant aluminum alloy.
[0007] Preferably, in step S1, the mass percentage of Fe in the above-mentioned waste aluminum-silicon alloy is 0.8% to 1.5%.
[0008] Preferably, in step S1, the mass percentage of Si in the above-mentioned waste aluminum-silicon alloy is 6.5% to 10%.
[0009] Preferably, in step S1, the melting temperature is 720°C to 740°C; and / or, The temperature at which complete melting occurs is 720℃~740℃; and / or, The solid phase fraction of the above-mentioned semi-solid slurry is 50%~60%.
[0010] Preferably, in step S1, the specific operation of the semi-solid sedimentation iron removal is as follows: the semi-solid slurry is subjected to constant temperature sedimentation under the action of a magnetic field, so that the iron-rich phase is separated by sedimentation.
[0011] Preferably, the semi-solid sedimentation iron removal is carried out in a double-layered nested crucible. The double-layered nested crucible comprises: The inner crucible is used to hold materials and has a flow guide hole at its bottom. The outer insulation component, nested outside the inner crucible, includes: a heating coil surrounding the outer periphery of the inner crucible, a vacuum container surrounding the heating coil, and an insulation layer between the heating coil and the vacuum container for heat insulation. An outer detachable crucible is disposed below the inner crucible and communicates with the inner crucible through the flow guide hole, and is used to receive the material flowing out through the flow guide hole; The outer detachable crucible and the inner crucible are connected by a detachable structure, which facilitates separation and material removal.
[0012] Preferably, in step S2, the above-mentioned recycled heat-resistant and creep-resistant aluminum alloy comprises, by mass percentage, the following components: Si: 7%~10%, Fe≤0.3%, Ta: 0.1%~0.18%, Nb: 0.12%~0.2%, Mn: 0.2%~0.5%, Cu: ≤0.2%, Ce and La combined: 0.05%~0.15%, Mg≤0.15%, balance Al and unavoidable impurities; impurities ≤0.1%; Furthermore, the mass ratio of Ta to Nb is (1~1.3):1, the mass ratio of Mn to Fe is (1.5~2):1, and the mass ratio of Ce to La is 2:1.
[0013] Preferably, in step S1, the above-mentioned recycled heat-resistant and creep-resistant aluminum alloy further includes one or more of the following components: Ti:0%~0.2%, Ni:0%~2.5%, Sn:0%~0.05%, Zn:0%~3%.
[0014] Secondly, this application provides a heat-resistant and creep-resistant aluminum alloy, which is prepared by the above method.
[0015] Thirdly, this application provides a heat-resistant and creep-resistant structural component, at least a portion of which is a recycled heat-resistant and creep-resistant aluminum alloy obtained by the above method, or is the above-mentioned heat-resistant and creep-resistant aluminum alloy.
[0016] In summary, the technical solutions conceived in this application have the following main technical advantages compared with the prior art: (1) The method for preparing recycled heat-resistant and creep-resistant aluminum alloys by semi-solid iron removal provided in this application effectively solves the technical problems of low iron removal efficiency, insufficient control of iron-rich phase, and high energy consumption in the recycling process by adopting a five-element composite system of Mn-Ce-La-Ta-Nb and accurately controlling the ratio between each component, combined with a semi-solid sedimentation iron removal process. In terms of iron removal, Mn reacts with Fe to generate α-Al(Mn,Fe)Si blocky phase, avoiding the formation of acicular β-AlFeSi brittle phase; Ce-La fully refines the iron-rich phase through grain boundary adsorption and transforms its morphology from acicular to granular; Ta-Nb synergistically forms dispersed particles, which can inhibit the adhesion and aggregation of iron-rich phase on the surface of Ta particles, avoiding local enrichment of iron-rich phase, thereby significantly improving iron removal efficiency and stably controlling the Fe residue. In terms of semi-solid settling, the modified melt is cooled to the semi-solid temperature range, and the iron-rich phase is caused to settle downward by utilizing the density difference between the iron-rich phase and the liquid aluminum-silicon matrix, thus achieving effective separation of the iron-rich phase. At the same time, semi-solid settling is carried out at a lower temperature, which significantly reduces energy consumption compared to traditional all-liquid smelting.
[0017] (2) During the semi-solid sedimentation process, Ta and Nb react in situ with Al to generate nanoscale Al3(Ta,Nb) composite reinforcing phases, which are uniformly dispersed in the aluminum matrix. By hindering dislocation movement and pinning grain boundaries, the room temperature tensile strength, elongation, and high-temperature creep resistance of the alloy are significantly improved. Thus, this application achieves efficient iron removal and low-energy recovery while synergistically improving the mechanical properties and heat resistance and creep resistance of the recovered alloy, breaking through the technical bottleneck of traditional recovery methods that cannot simultaneously achieve iron removal and strengthening.
[0018] (3) This application uses a double-layer nested crucible for semi-solid sedimentation iron removal. Through a simplified partitioning design of the inner crucible for liquid storage and the outer crucible for slag storage, combined with the semi-solid sedimentation process, it achieves directional separation of the iron-rich phase and low-disturbance liquid extraction, effectively solving the problems of high equipment cost, long cleaning time, and easy mixing of iron-rich phase into the liquid in the prior art. The crucible has fewer parts, shorter assembly time, lower unit cost, and is easy to clean, significantly reducing equipment investment and operation difficulty.
[0019] (4) The recycling process of this application is stable and has high production efficiency, and is applicable to common waste aluminum-silicon alloys. Semi-solid sedimentation combined with magnetic field-assisted sedimentation shortens the sedimentation time and the production cycle of a single batch, which is conducive to continuous industrial production. At the same time, the recycling method of this application does not require changes to the existing melting equipment, the modification cost is low and the cycle is short, and the product performance meets the needs of heat-resistant and creep-resistant aluminum alloys in the fields of new energy vehicles, aerospace and other fields, and has broad industrial promotion value.
[0020] (5) The recycled heat-resistant and creep-resistant aluminum alloy obtained in this application has a stable Fe residual content of ≤0.3%, a room temperature ultimate tensile strength >310MPa, a room temperature yield strength >210MPa, a room temperature elongation >10%, and a minimum steady-state creep rate <10 at 250℃ and 50MPa. -9 S -1 Its comprehensive mechanical properties are significantly better than those of composite modified aluminum-silicon alloys produced by traditional recycling processes, and it can replace virgin aluminum alloys for high-end heat-resistant structural components. Attached Figure Description
[0021] Figure 1 This is a schematic diagram of the process for preparing recycled heat-resistant and creep-resistant aluminum alloys by semi-solid iron removal provided in this application; Figure 2 This is a cross-sectional view of the double-layer nested crucible used in the embodiments of this application; Figure 3 This is a microscopic morphology image of the recycled heat-resistant and creep-resistant aluminum alloy obtained in Example 1 of this application; In all the accompanying drawings, the same reference numerals are used to denote the same elements or structures, wherein: 1 is the inner crucible; 2 is the heating coil; 3 is the vacuum vessel; 4 is the insulation layer; 5 is the flow guide hole; and 6 is the outer detachable crucible. Detailed Implementation
[0022] To make the objectives, technical solutions, and advantages of this application clearer, the following detailed description is provided in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.
[0023] In the description of this application, it should be understood that the term "and / or" describes a relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. The symbol " / " in this document indicates that the related objects are in an "or" relationship; for example, A / B means A or B.
[0024] In the description of the embodiments in this application, the words "exemplary" or "for example" are used to indicate that they are examples, illustrations, or descriptions. Any embodiment or design that is described as "exemplary" or "for example" in the embodiments of this application should not be construed as being more preferred or advantageous than other embodiments or design options. Specifically, the use of the words "exemplary" or "for example" is intended to present the relevant concepts in a specific manner.
[0025] In the description of the embodiments in this application, unless otherwise stated, "multiple" means two or more.
[0026] like Figure 1As shown, this application provides a method for preparing recycled heat-resistant and creep-resistant aluminum alloys through semi-solid iron removal, comprising the following steps: S1. The waste aluminum-silicon alloy is melted to obtain a melt, and then a composite modifier containing Mn, Ce, La, Ta and Nb elements is added. After it is completely melted, it is cooled to obtain a semi-solid slurry, and then semi-solid sedimentation is carried out to remove iron. The mass ratio of Mn to Fe in the waste aluminum-silicon alloy is (0.9~1.1):1; the mass ratio of Ta to Fe in the waste aluminum-silicon alloy is (0.05~0.2):1; the total mass ratio of La and Ce to the waste aluminum-silicon alloy is (0.1~0.15):100; and the mass ratio of Nb to Ta is (1~1.2):1; the mass ratio of La to Ce is 1:2. S2. Take the upper melt and cast it to obtain a recycled heat-resistant and creep-resistant aluminum alloy.
[0027] In some embodiments, in step S1, the mass percentage of Fe in the aforementioned waste aluminum-silicon alloy is 0.8% to 1.5%.
[0028] In some embodiments, in step S1, the mass percentage of Si in the aforementioned waste aluminum-silicon alloy is 6.5% to 10%.
[0029] In some implementations, the mass ratio of Mn to Fe in the waste aluminum-silicon alloy is (0.9~1.1):1, for example, 0.9:1, 1:1, 1.1:1, etc.
[0030] In some implementations, the mass ratio of Ta to Fe in the waste aluminum-silicon alloy is (0.05~0.2):1, for example, 0.05:1, 0.08:1, 0.1:1, 0.12:1, 0.15:1, 0.18:1, 0.2:1, etc.
[0031] In some implementations, the total mass ratio of La and Ce to the mass of the waste aluminum-silicon alloy is (0.1~0.15):100, that is, the total amount of La and Ce is 0.1wt%~0.15wt% of the mass of the waste aluminum-silicon alloy, specifically 0.1wt%, 0.11wt%, 0.12wt%, 0.13wt%, 0.14wt%, 0.15wt%, etc.
[0032] The method for preparing recycled heat-resistant and creep-resistant aluminum alloys by semi-solid iron removal provided in this application adopts a five-element composite modification system of Mn-Ce-La-Ta-Nb and controls the proportion and amount of each element to control the iron removal efficiency of waste aluminum-silicon alloys and the mechanical properties and high-temperature creep resistance of the recovered aluminum-silicon alloys, thereby achieving efficient iron removal and improving the room temperature mechanical properties and creep resistance of the obtained alloys.
[0033] On the one hand, by controlling the appropriate ratio of Mn to Fe, Mn preferentially reacts with Fe in the melt to form α-Al(Mn,Fe)Si bulk phase, maximizing the proportion of bulk phase formation and avoiding the formation of acicular β-AlFeSi brittle phase. On the other hand, by controlling the specific ratio and total amount of Ce and La, the iron-rich phase can be refined to 7~11μm through grain boundary adsorption, and its morphology can be transformed from acicular to granular. At the same time, by controlling the appropriate ratio of Nb to Ta and the amount of Ta added, Nb reacts with free oxygen in the melt to form a dense Nb2O5 oxide film, which protects Ta and makes Ta exist stably in the melt. This allows Ta-Nb to synergistically form dispersed particles, which can inhibit the adhesion and aggregation of iron-rich phase on the surface of Ta particles, avoid local enrichment of iron-rich phase, and thus control the Fe residue to ≤0.3% and increase the iron removal rate to ≥85%.
[0034] On the other hand, by controlling the amount and ratio of Nb and Ta, Ta and Nb react with Al in situ to generate a nanoscale (20~40nm) Al3(Ta,Nb) composite reinforcing phase. This phase is uniformly dispersed in the aluminum matrix and significantly improves the creep resistance of the recycled alloy at high temperatures by hindering dislocation movement and pinning grain boundaries.
[0035] In some embodiments, the composite modifier includes raw materials containing Mn, Ce, La, Ta, and Nb. It is understood that this application does not limit the form of the above raw materials; they can be alloys or pure metals containing the above elements, as long as the composition of the aluminum-silicon alloy obtained after melting the added raw materials is within the range defined in this application. In some embodiments, the composite modifier may include pure Mn or Mn alloys, pure Ce or Ce alloys, pure La or La alloys, pure Ta or Ta alloys, and pure Nb or Nb alloys. In some specific embodiments of this application, the above raw materials include pure Mg, cerium-lanthanum alloys, and aluminum-tantalum-niobium alloys.
[0036] In some embodiments, in step S1, the melting temperature is 720°C to 740°C.
[0037] In some embodiments, in step S1, the temperature at which complete melting occurs is 720°C to 740°C, and the holding time is 15 to 25 minutes.
[0038] In some embodiments, in step S1, after the composite modifier has completely melted, the melt is cooled to the semi-solid temperature range (590℃~610℃) so that the solid phase ratio of the semi-solid slurry is controlled at 50%~60%.
[0039] This application utilizes the semi-solid sedimentation of the modified melt, taking advantage of the fact that the high-melting-point iron-rich phase exists in solid form at this temperature while the aluminum-silicon matrix remains liquid. This creates a density difference between the solid iron-rich phase and the liquid matrix, causing the iron-rich phase to settle downwards under gravity, thus achieving effective separation from the low-iron melt. Simultaneously, it avoids insufficient sedimentation due to excessively low solids content or suspension of the iron-rich phase due to excessively high solids content. Furthermore, this solids content facilitates the supersaturated precipitation of Ta and Nb, which then combine with Al to form an Al3(Ta,Nb) composite strengthening phase in situ. The precipitation rate and diffusion path can be controlled, ensuring a uniform and dispersed distribution, avoiding local aggregation or coarsening, thereby achieving optimal strengthening effect and effectively improving the alloy's high-temperature creep resistance. By combining five-element composite modification with semi-solid sedimentation, the problems of large Ta strengthening element burn-off and incomplete iron-rich phase separation in traditional processes are avoided. This achieves a balance between iron removal, strengthening, and process stability, offering advantages such as simple process, low energy consumption, and high iron removal efficiency, making it suitable for industrial application.
[0040] In some embodiments, in step S1, the specific operation of the semi-solid sedimentation iron removal is as follows: the semi-solid slurry is subjected to constant temperature sedimentation under the action of a magnetic field, so that the iron-rich phase is separated by sedimentation.
[0041] In some embodiments, the strength of the magnetic field can be 0.4T to 0.5T. Those skilled in the art will understand that adaptively adjusting the strength of the magnetic field to control the iron settling rate based on factors such as the temperature of the melt being processed, the iron content, viscosity, the size of the processing container, or the melt flow rate is within the scope of protection of this application.
[0042] In some embodiments, the semi-solid sedimentation iron removal is carried out in a double-layered nested crucible. The double-layered nested crucible includes: The inner crucible is used to hold materials and has a flow guide hole at its bottom. The outer insulation component, nested outside the inner crucible, includes: a heating coil surrounding the outer periphery of the inner crucible, a vacuum container surrounding the heating coil, and an insulation layer between the heating coil and the vacuum container for heat insulation. An outer detachable crucible is disposed below the inner crucible and communicates with the inner crucible through the flow guide hole, and is used to receive the material flowing out through the flow guide hole; The outer detachable crucible and the inner crucible are connected by a detachable structure, which facilitates separation and material removal.
[0043] The double-layer nested crucible designed in this application has a simple structure, low cost, and is easy to clean, significantly reducing equipment investment and operational difficulty. Through a partitioned design with an inner crucible storing liquid and an outer crucible storing slag, combined with a semi-solid sedimentation process, the iron-rich phase is directionally separated, and the liquid extraction process remains undisturbed, further ensuring the stability of Fe residue levels.
[0044] In some embodiments, in step S2, the casting process includes, but is not limited to, squeeze casting, gravity casting, die casting, etc.
[0045] In some embodiments, in step S2, the above-mentioned recycled heat-resistant and creep-resistant aluminum alloy, by mass percentage, comprises the following components: Si: 7%~10%, Fe≤0.3%, Ta: 0.1%~0.18%, Nb: 0.12%~0.2%, Mn: 0.2%~0.5%, Cu: ≤0.2%, Ce and La sum: 0.05%~0.15%, Mg≤0.15%, with the balance being Al and unavoidable impurities; impurities ≤0.1%. Furthermore, the mass ratio of Ta to Nb is (1~1.3):1, the mass ratio of Mn to Fe is (0.8~1.5):1, and the mass ratio of Ce to La is 2:1.
[0046] It is understandable that the recycled raw materials may originate from different grades (e.g., but not limited to A356, A357, A380, ADC12, AlSi10MnMg, etc.) of aluminum-silicon alloys or mixtures thereof. In addition to the aforementioned elemental components, these grades may also contain other elements permitted by their respective standards or introduced concurrently. Therefore, the recycled heat-resistant and creep-resistant aluminum alloys obtained in this application may contain one or more of the following components, in addition to the aforementioned components, with the following content as a percentage by mass: Ti: 0%~0.2%, Ni: 0%~2.5%, Sn: 0%~0.05%, Zn: 0%~3%, etc. When the recycled heat-resistant and creep-resistant aluminum alloy does not contain one or more of the aforementioned elements, its mass percentage is 0%.
[0047] This application also provides a heat-resistant and creep-resistant aluminum alloy, which is prepared by the above method.
[0048] In some embodiments, the above-mentioned heat-resistant and creep-resistant aluminum alloy has a room temperature ultimate tensile strength > 310 MPa, a room temperature yield strength > 210 MPa, and a room temperature elongation > 10%.
[0049] In some embodiments, the minimum steady-state creep rate of the above-mentioned heat-resistant and creep-resistant aluminum alloy at 250°C and 50MPa is <10. -9 ·S -1 .
[0050] The recycled heat-resistant and creep-resistant aluminum alloy obtained in this application possesses excellent mechanical properties and high creep resistance, making it suitable for use as heat-resistant and creep-resistant structural components. Based on this, this application provides a heat-resistant and creep-resistant structural component, at least a portion of which is the recycled heat-resistant and creep-resistant aluminum alloy obtained by the above method, or is one of the aforementioned heat-resistant and creep-resistant aluminum alloys. It is understood that the structural component can be entirely manufactured from the aforementioned composite modified aluminum-silicon alloy; alternatively, it can be partially manufactured from the aforementioned composite modified aluminum-silicon alloy and partially from other materials (such as plastics, other metal materials, etc.), depending on the specific application requirements.
[0051] It is understood that this application does not particularly limit the specific types of the aforementioned structural components, and they can be any structural component suitable for aluminum alloy manufacturing. Furthermore, the structure and properties of this structural component can be referenced from conventional techniques, and will not be elaborated further here. For example, this structural component can be applied in new energy vehicles as an automotive structural component, such as the entire vehicle body, rear wheel arch inner panel, rear longitudinal beam, floor connecting plate, rear floor plate, beam internal reinforcing plate, hood, mudguards, doors, rear cargo box, and roof, etc.
[0052] It should be understood that materials of the same or similar type, model, quality, properties, or function as those used in the following embodiments can be used to implement this application. Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods. Unless otherwise specified, the materials, reagents, etc., used in the following embodiments are commercially available.
[0053] The following are examples and comparative examples: Example 1 The method for preparing recycled heat-resistant and creep-resistant aluminum alloys by semi-solid iron removal provided in this embodiment includes the following steps: (1) Preparation of waste aluminum alloy melt: In this embodiment, waste A356 alloy with a Fe mass percentage of 1% is used as the recycling object. 100kg of waste A356 alloy is placed in a crucible, heated to 730℃ to melt, and 0.6L / min of argon gas is introduced to obtain waste aluminum-silicon alloy melt.
[0054] (2) Five-element composite modification: 0.8 kg of pure Mn ingot, 0.11 kg of Ce-La alloy (Ce:La mass ratio of 2:1), and 2.2 kg of Al-5Ta-6Nb ternary alloy (Ta mass percentage of 5% and Nb mass percentage of 6% in the ternary alloy) were added to the above-mentioned waste aluminum-silicon alloy melt and held at 730℃ for 20 min to allow the composite modifier to completely melt. That is, the mass ratio of the modifying element Mn to Fe in the waste aluminum-silicon alloy is 0.8:1, the mass ratio of the modifying element Ta to Fe in the waste aluminum-silicon alloy is 0.11:1, the mass ratio of Nb to Ta is 1.2:1, and the amount of Ce-La alloy used is 0.11 wt% of the mass of the waste aluminum-silicon alloy.
[0055] (3) Semi-solid sedimentation separation and iron removal: The composite modified melt is transferred into the inner crucible 1 of the double-layer nested crucible, and its cross-sectional view is shown in the figure. Figure 2 As shown, heating is achieved using a heating coil 2 located around the inner crucible 1, while a vacuum tank 3 is located outside the heating coil 2, forming an effective heat insulation layer 4 around the inner crucible. This cools the composite-modified melt to 600℃, forming a semi-solid slurry with a solid phase content of 60%. Then, a 0.45T magnetic field is applied for constant-temperature sedimentation for 30 minutes. The guide hole 5 at the bottom of the inner crucible is then opened, allowing the iron-rich phase to fall through the bottom hole of the inner crucible into the annular slag storage area of the outer separable crucible 6, completing the sedimentation and separation of the iron-rich phase.
[0056] (4) Casting: Close the flow guide hole at the bottom of the inner crucible, use an argon protective spoon (flow rate of 0.15L / min) to take 92.8kg of liquid at 1.0L / min, cast it, and cool it to obtain the composite modified aluminum-silicon alloy.
[0057] The composition of the composite modified aluminum-silicon alloy was tested and, by mass percentage, included the following components: 0.21% Fe, 6.8% Si, 0.3% Mg, 0.15% Cu, 0.8% Mn, 0.1% Zn, 0.15% Ti, 0.11% Ta, 0.13% Nb, 0.073% Ce, 0.037% La, 0.13% other impurities, with the balance being Al. Figure 3 The microstructure (SEM image) of the composite modified aluminum-silicon alloy shows that Ta-Nb and Al form an Al3(Ta,Nb) composite reinforcing phase in situ, with a particle size of 20~40 nm.
[0058] (5) Recycling: To evaluate the recycling performance of the composite modified aluminum-silicon alloy provided in this embodiment, the above-mentioned composite modified aluminum-silicon alloy was placed in a crucible as recycling waste and completely melted to obtain a remelted melt. The Fe content in the remelted melt was detected to determine whether to add a five-element composite modification system. If the Fe content is ≤0.3%, there is no need to add a five-element composite modification system, and the remelted melt is directly cast into shape in step (4) to complete one recycling. Considering that Fe will gradually accumulate during the recycling process, when the content exceeds 0.3%, the above steps (1) to (4) are followed for melting, five-element composite modification, and semi-solid sedimentation separation to remove iron. The recycling steps are repeated five times to obtain the fifth batch of composite modified aluminum-silicon alloy.
[0059] Example 2 The method for preparing recycled heat-resistant and creep-resistant aluminum alloys by semi-solid iron removal provided in this embodiment includes the following steps: (1) Preparation of waste aluminum alloy melt: In this embodiment, waste A380 alloy with Fe mass percentage of 1.3% is used as the recycling object. 100kg of waste A380 aluminum-silicon alloy is placed in a crucible, heated to 730℃ to melt, and 0.6L / min of argon gas is introduced to obtain waste aluminum-silicon alloy melt.
[0060] (2) Five-element composite modification: 1.3 kg of pure Mn ingot, 0.12 kg of Ce-La alloy (Ce:La mass ratio of 2:1), and 1.3 kg of Al-5Ta-6Nb ternary alloy (Ta mass percentage of 5% and Nb mass percentage of 6% in the ternary alloy) were added to the above-mentioned waste aluminum-silicon alloy melt and held at 730℃ for 20 min to allow the composite modifier to completely melt. That is, the mass ratio of the modifying element Mn to Fe in the waste aluminum-silicon alloy is 1:1, the mass ratio of the modifying element Ta to Fe in the waste aluminum-silicon alloy is 0.05:1, the mass ratio of Nb to Ta is 1.2:1, and the amount of Ce-La alloy used is 0.12 wt% of the mass of the waste aluminum-silicon alloy.
[0061] (3) Semi-solid sedimentation separation to remove iron: The composite modified melt is transferred into the inner crucible of the double-layer nested crucible. The composite modified melt is cooled to 600℃ by heating coils set around the inner crucible to form a semi-solid slurry with a solid phase of 60%. Then, a magnetic field of 0.45T is applied for constant temperature sedimentation for 30 minutes. The guide hole at the bottom of the inner crucible is opened so that the iron-rich phase falls into the annular slag storage area of the outer crucible through the bottom hole of the inner crucible, thus completing the sedimentation separation of the iron-rich phase.
[0062] (4) Casting: Close the flow guide hole at the bottom of the inner crucible, use an argon protective spoon (flow rate of 0.15L / min) to take 92.8kg of liquid at 1.0L / min, cast it, and cool it to obtain the composite modified aluminum-silicon alloy.
[0063] The composite modified aluminum-silicon alloy was analyzed for composition, and by mass percentage, it included the following components: 0.25% Fe, 7.6% Si, 0.1% Mg, 3.1% Cu, 1.3% Mn, 0.15% Ti, 2.1% Zn, 0.4% Ni, 0.23% Sn, 0.05% Ta, 0.06% Nb, 0.08% Ce, 0.04% La, 0.33% other impurities, with the balance being Al.
[0064] (5) Recycling: The above-mentioned composite modified aluminum-silicon alloy is recycled according to the method provided in Example 1 to obtain the fifth batch of composite modified aluminum-silicon alloy.
[0065] Example 3 The method for preparing recycled heat-resistant and creep-resistant aluminum alloys by semi-solid iron removal provided in this embodiment includes the following steps: (1) Preparation of waste aluminum alloy melt: In this embodiment, waste ADC12 alloy with Fe mass percentage of 1.3% is used as the recycling object. 100kg of waste ADC12 alloy is placed in a crucible, heated to 730℃ to melt, and 0.6L / min of argon gas is introduced to obtain waste aluminum-silicon alloy melt.
[0066] (2) Five-element composite modification: 1.95 kg of pure Mn ingot, 0.12 kg of Ce-La alloy (Ce:La mass ratio of 2:1), and 6 kg of Al-5Ta-6Nb ternary alloy (Ta mass percentage of 5% and Nb mass percentage of 6% in the ternary alloy) were added to the above-mentioned waste aluminum-silicon alloy melt and held at 730℃ for 20 min to allow the composite modifier to completely melt. That is, the mass ratio of the modifying element Mn to Fe in the waste aluminum-silicon alloy is 1.5:1, the mass ratio of the modifying element Ta to Fe in the waste aluminum-silicon alloy is 0.2:1, the mass ratio of Nb to Ta is 1:1, and the amount of Ce-La alloy used is 0.15 wt% of the mass of the waste aluminum-silicon alloy.
[0067] (3) Semi-solid sedimentation separation to remove iron: The composite modified melt is transferred into the inner crucible of the double-layer nested crucible. The composite modified melt is cooled to 600℃ by heating coils set around the inner crucible to form a semi-solid slurry with a solid phase of 60%. Then, a magnetic field of 0.45T is applied for constant temperature sedimentation for 30 minutes. The guide hole at the bottom of the inner crucible is opened so that the iron-rich phase falls into the annular slag storage area of the outer crucible through the bottom hole of the inner crucible, thus completing the sedimentation separation of the iron-rich phase.
[0068] (4) Casting: Close the flow guide hole at the bottom of the inner crucible, use an argon protective spoon (flow rate of 0.15L / min) to take 92.8kg of liquid at 1.0L / min, cast it, and cool it to obtain the composite modified aluminum-silicon alloy.
[0069] The composite modified aluminum-silicon alloy was subjected to compositional testing, and the composition, by mass percentage, included the following components: 0.27% Fe, 9.8% Si, 0.3% Mg, 3% Cu, 1.65% Mn, 0.15% Zn, 0.15% Ti, 0.3% Ni, 0.15% Ta, 0.15% Nb, 0.1% Ce, 0.05% La, 0.27% other impurities, with the balance being Al.
[0070] (5) Recycling: The above-mentioned composite modified aluminum-silicon alloy is recycled according to the method provided in Example 1 to obtain the fifth batch of composite modified aluminum-silicon alloy.
[0071] Comparative Example 1 The method for preparing recycled heat-resistant and creep-resistant aluminum alloy by semi-solid iron removal provided in this comparative example is the same as that in Example 1, except that the composite modifier does not contain Ta and Nb elements, and a modified aluminum-silicon alloy is prepared. Then, the modified aluminum-silicon alloy is recycled according to the method provided in Example 1 to obtain the modified aluminum-silicon alloy produced in the fifth batch.
[0072] Comparative Example 2 The method for preparing recycled heat-resistant and creep-resistant aluminum alloy using semi-solid iron removal provided in this comparative example is the same as in Example 1, except that the composite modifier does not contain Ce and La elements, and a modified aluminum-silicon alloy is prepared. Then, the modified aluminum-silicon alloy is recycled according to the method provided in Example 1 to obtain the fifth batch of modified aluminum-silicon alloy.
[0073] Comparative Example 3 The method for preparing recycled heat-resistant and creep-resistant aluminum alloy by semi-solid iron removal provided in this comparative example is the same as that in Example 1, except that the composite modifier does not contain Nb element, and a modified aluminum-silicon alloy is prepared. Then, the modified aluminum-silicon alloy is recycled according to the method provided in Example 1 to obtain the modified aluminum-silicon alloy produced in the fifth batch.
[0074] Comparative Example 4 The method for preparing recycled heat-resistant and creep-resistant aluminum alloy by semi-solid iron removal provided in this comparative example is the same as that in Example 1, except that the amount of Al-5Ta-6Nb ternary alloy (the mass percentage of Ta in the ternary alloy is 5% and the mass percentage of Nb is 6%) used in step (2) is 0.4 kg. That is, the mass ratio of the modifying element Ta to Fe in the waste aluminum-silicon alloy is 0.02:1, and the modified aluminum-silicon alloy is prepared. Then, the modified aluminum-silicon alloy is recycled according to the method provided in Example 1 to obtain the modified aluminum-silicon alloy produced in the fifth batch.
[0075] Comparative Example 5 The method for preparing recycled heat-resistant and creep-resistant aluminum alloy by semi-solid iron removal provided in this comparative example is the same as that in Example 1, except that the Al-Ta-Nb ternary alloy in step (2) is Al-6Ta-5Nb. That is, the mass ratio of the modifying element Nb to Ta is approximately 0.8:1, and a modified aluminum-silicon alloy is prepared. Then, the modified aluminum-silicon alloy is recycled according to the method provided in Example 1 to obtain the modified aluminum-silicon alloy produced for the fifth time.
[0076] Comparative Example 6 The method for preparing recycled heat-resistant and creep-resistant aluminum alloy by semi-solid iron removal provided in this comparative example is the same as that in Example 1, except that the Al-Ta-Nb ternary alloy in step (2) is Al-4Ta-7Nb. The mass ratio of the modifying element Nb to Ta is 1.5:1.
[0077] Performance testing: A. Mechanical properties at room temperature Referring to standard GB / T228.1-2021, the mechanical properties of the composite modified aluminum-silicon alloys prepared in Examples 1-3 and the fifth production of the composite modified aluminum-silicon alloy, as well as the modified aluminum-silicon alloys prepared in Examples 1-6 and the fifth production of the modified aluminum-silicon alloy, were tested. Ten specimens were taken for each alloy, and the average value of the results was taken.
[0078] B. Creep resistance Referring to the standard GB / T 2039-2024, the creep performance of the composite modified aluminum-silicon alloys prepared in Examples 1-3 and the fifth production was tested under the conditions of 250℃ and 50MPa. The creep performance of the modified aluminum-silicon alloys prepared in Comparative Examples 1-6 and the fifth production was also tested. The minimum steady-state creep rate was determined based on the slope of the steady-state stage of the creep curve. Ten specimens were used for each alloy, and the average value of the results was taken.
[0079] The test results are shown in Table 1.
[0080]
[0081]
[0082] As shown in Table 1, compared to Comparative Examples 1-6, the method for preparing recycled heat-resistant and creep-resistant aluminum alloys through semi-solid iron removal provided in this application, by employing a Mn-Ce-La-Ta-Nb pentagonal composite modification system, can significantly improve the mechanical properties, creep resistance, and iron removal efficiency of the alloy. Regarding the iron removal effect, the Fe mass percentage (Fe residue) in the recovered composite modified aluminum-silicon alloys in the examples is as low as 0.21%, and the iron removal rate is ≥85%. Furthermore, the recovered composite modified aluminum-silicon alloys have a room temperature ultimate tensile strength >310 MPa, a room temperature yield strength >210 MPa, and a room temperature elongation >10%, exhibiting high strength and high toughness. In addition, the minimum steady-state creep rate of the above-mentioned composite modified aluminum-silicon alloys under conditions of 250℃ and 50 MPa is less than 10. -9 S -1 It exhibits excellent heat resistance and creep resistance, making it suitable for high-end heat-resistant applications. The above data shows that this application achieves excellent iron removal effect, high mechanical properties, and strong heat resistance and creep resistance through the synergistic effect of each component (Mn, Ce, La, Ta, Nb) in the five-element composite modification system and the precise control of the component distribution ratio, thereby preparing a recycled heat-resistant and creep-resistant aluminum alloy.
[0083] Comparing Example 1 and Comparative Example 4, it can be seen that the Fe residual content in Comparative Example 4 is significantly increased, and the mechanical properties and creep resistance are significantly decreased. The reason for this may be that when the mass ratio of Ta in the composite modifier to Fe in the waste aluminum-silicon alloy is less than 0.05:1 (the mass ratio of the modifying element Ta to Fe in the waste aluminum-silicon alloy in Comparative Example 4 is 0.02:1), the Ta-Nb synergistic modification system fails. On the one hand, the insufficient number of Ta-Nb dispersed particles weakens the inhibitory effect on the heterogeneous nucleation and growth of the iron-rich phase, leading to coarsening and segregation of the iron-rich phase and an increase in Fe residual content. On the other hand, the insufficient generation of Al3(Ta,Nb) nano-reinforcing phase fails to effectively pin dislocations and grain boundaries, ultimately resulting in a significant decrease in both the room-temperature mechanical properties and high-temperature creep resistance of the alloy.
[0084] Comparing Example 1 with Comparative Examples 5 and 6, it can be seen that the Fe residue content is increased and the mechanical properties are decreased in Comparative Examples 5 and 6. The reason for this may be that when the Nb / Ta mass ratio is too small (the Nb / Ta mass ratio in Comparative Example 5 is 0.8:1), the amount of Nb is relatively insufficient compared to Ta, making it difficult to form a continuous and dense Nb2O5 protective film on the melt surface and the Ta particle surface. Some Ta undergoes oxidation and burn-off, resulting in a reduction in the number of dispersed particles formed by Ta-Nb synergy. This weakens the inhibitory effect on the adhesion and aggregation of the iron-rich phase on the Ta particle surface, preventing the iron-rich phase from effectively settling and separating, leading to an increase in Fe residue and a worse iron removal effect. At the same time, the Ta-Nb solid solution is not fully formed, and the Al3(Ta,Nb) composite reinforcing phase is insufficient in quantity and unevenly distributed, failing to effectively pin grain boundaries and hinder dislocation movement. Ultimately, this results in a decrease in the elongation and a deterioration in the creep resistance of the recovered composite modified aluminum-silicon alloy. When the Nb / Ta mass ratio is too high (the Nb / Ta mass ratio in Comparative Example 6 is 1.5:1), the excess Nb cannot be completely dissolved or enter the Al3(Ta,Nb) phase. Instead, it reacts with elements such as Al and Si to form coarse Nb-containing intermetallic compounds (such as Al3Nb and Al-Nb-Si phases). These coarse phases become stress concentration points and crack initiation sources, deteriorating the strength and plasticity of the alloy. At the same time, the excess Nb interferes with the grain boundary adsorption and refinement effect of Ce-La on the iron-rich phase, resulting in coarse iron-rich phases, increased Fe residue, and decreased elongation.
[0085] Furthermore, the composite modified aluminum-silicon alloy (i.e., the recycled heat-resistant and creep-resistant aluminum alloy) produced in the first stage of the embodiment was recycled. The Fe content in the fifth stage composite modified aluminum-silicon alloy was still effectively controlled within the range of ≤0.3%, and it still exhibited excellent room temperature mechanical properties and high temperature creep resistance. This indicates that the five-element composite modification strategy adopted in this application can effectively suppress the coarsening and aggregation of harmful iron-rich phases (such as acicular β-AlFeSi phase) during the remelting process, delay the cumulative deterioration effect of impurity element Fe, and ensure that the alloy maintains a dense microstructure and stable strengthening phase distribution after the fifth recycling. This strategy not only reduces the dependence on frequent addition of modifiers and deep iron removal operations during the recycling process, but also significantly improves the technical and economic efficiency of closed-loop regeneration of aluminum alloys, providing a reliable technical path for the high-value and low-carbon utilization of waste aluminum-silicon alloys.
[0086] Those skilled in the art will readily understand that the above description is merely a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. A method for preparing recycled heat-resistant and creep-resistant aluminum alloys through semi-solid iron removal, characterized in that, Includes the following steps: S1. The waste aluminum-silicon alloy is melted to obtain a melt, and then a composite modifier containing Mn, Ce, La, Ta and Nb elements is added. After it is completely melted, it is cooled to obtain a semi-solid slurry, and then semi-solid sedimentation is carried out to remove iron. The mass ratio of Mn to Fe in the waste aluminum-silicon alloy is (0.8~1.5):1, the mass ratio of Ta to Fe in the waste aluminum-silicon alloy is (0.05~0.2):1, and the total amount of Ce and La is 0.1wt%~0.15wt% of the mass of the waste aluminum-silicon alloy; furthermore, the mass ratio of Nb to Ta is (1~1.2):1, and the mass ratio of Ce to La is 2:
1. S2. Take the upper melt and cast it to obtain a recycled heat-resistant and creep-resistant aluminum alloy.
2. The method according to claim 1, characterized in that, In step S1, the mass percentage of Fe in the waste aluminum-silicon alloy is 0.8% to 1.5%.
3. The method according to claim 2, characterized in that, The waste aluminum-silicon alloy contains 6.5% to 10% Si by mass.
4. The method according to claim 1 or 2, characterized in that, The melting temperature is 720℃~740℃; and / or, The temperature at which complete melting occurs is 720℃~740℃; and / or, The solid phase content of the semi-solid slurry is 50%~60%.
5. The method according to claim 1, characterized in that, The specific operation of the semi-solid sedimentation iron removal is as follows: the semi-solid slurry is subjected to constant temperature sedimentation under the action of a magnetic field, so that the iron-rich phase is separated by sedimentation.
6. The method according to claim 5, characterized in that, The semi-solid sedimentation iron removal is carried out in a double-layered nested crucible; the double-layered nested crucible includes: The inner crucible (1) is used to hold materials, and a flow guide hole (5) is provided at its bottom. The outer insulation component, nested outside the inner crucible (1), includes: a heating coil (2) surrounding the outer periphery of the inner crucible (1), a vacuum tank (3) surrounding the outer periphery of the heating coil (2), and an insulation layer (4) between the heating coil (2) and the vacuum tank (3) for heat insulation; An outer separable crucible (6) is disposed below the inner crucible (1) and communicates with the inner crucible (1) through the flow guide hole (5) to receive the material flowing out through the flow guide hole; The outer detachable crucible (6) and the inner crucible (1) are connected by a detachable structure, which facilitates separation and material removal.
7. The method according to claim 1 or 2, characterized in that, In step S2, the recycled heat-resistant and creep-resistant aluminum alloy comprises the following components by mass percentage: Si: 7%~10%, Fe≤0.3%, Ta: 0.1%~0.18%, Nb: 0.12%~0.2%, Mn: 0.2%~0.5%, Cu: ≤0.2%, Ce and La combined: 0.05%~0.15%, Mg≤0.15%, balance Al and unavoidable impurities; impurities ≤0.1%; Furthermore, the mass ratio of Ta to Nb is (1~1.3):1, the mass ratio of Mn to Fe is (1.5~2):1, and the mass ratio of Ce to La is 2:
1.
8. The method according to claim 7, characterized in that, The recycled heat-resistant and creep-resistant aluminum alloy also includes one or more of the following components: Ti:0%~0.2%, Ni:0%~2.5%, Sn:0%~0.05%, Zn:0%~3%.
Citation Information
Patent Citations
Regeneration method of aluminum-silicon alloy, regenerated silicon-aluminum alloy and iron-rich phase alloy
CN119640072A